The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1113/ep087027
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dyssynchrony during hypoxic breathing but not during exercise in healthy subjects: a speckle tracking echocardiography study

Abstract: Pulmonary hypertension (PH) has been shown to be associated with regional inhomogeneity (or dyssynchrony) of right ventricular (RV) contraction. Right ventricular dyssynchrony is an independent predictor of decreased survival in advanced PH, but has also been reported in patients with only mildly elevated pulmonary artery pressure (PAP). The mechanisms of RV dyssynchrony in PH remain uncertain. Our aim was to evaluate RV regional function in healthy subjects during acute hypoxia and during exercise. Seventeen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Not surprisingly, the absence of RV overload as a contributor to the incidence of RVD may be explained by the fact that the elevated PAP during the first few days at HA was moderate. Consistently, recent results also showed that acute hypoxia for several minutes, but not exercise, could induce regional inhomogeneity (or dyssynchrony) of RV contraction, although both acute hypoxia and exercise led to a comparable increase in RV afterload, suggesting that acute hypoxia was the main determinant of RVD but not RV afterload (Pezzuto et al, 2018). Hypobaric hypoxia is the main characteristic of the HA environment but may result in the reduction in cardiac phosphocreatine (PCr)/ATP in healthy volunteers (Holloway et al, 2011).…”
Section: Determinants Of Ha Exposure-induced Rvdmentioning
confidence: 55%
See 1 more Smart Citation
“…Not surprisingly, the absence of RV overload as a contributor to the incidence of RVD may be explained by the fact that the elevated PAP during the first few days at HA was moderate. Consistently, recent results also showed that acute hypoxia for several minutes, but not exercise, could induce regional inhomogeneity (or dyssynchrony) of RV contraction, although both acute hypoxia and exercise led to a comparable increase in RV afterload, suggesting that acute hypoxia was the main determinant of RVD but not RV afterload (Pezzuto et al, 2018). Hypobaric hypoxia is the main characteristic of the HA environment but may result in the reduction in cardiac phosphocreatine (PCr)/ATP in healthy volunteers (Holloway et al, 2011).…”
Section: Determinants Of Ha Exposure-induced Rvdmentioning
confidence: 55%
“…In patients with pulmonary hypertension (PH), the presence of RVD is always associated with the symptomatology, functional state, exercise performance, and clinical outcomes (Murata et al, 2017;Rehman et al, 2018). Recent evidence also showed that RVD occurred during hypoxia but not during exercise, suggesting the combined contributions of mechanical (RV afterload) and systemic (hypoxia) factors (Pezzuto et al, 2018). Based on these reasons, we hypothesize that RVD is present under acute HA exposure and can be explained by HA hypoxia or increased RV afterload.…”
Section: Introductionmentioning
confidence: 99%
“…International Ltd, Southam, UK), producing a fraction of inspired oxygen (F iO 2 ) of 12%. This degree of hypoxia corresponds to an altitude of 4500 m and has been shown to be well tolerated with minimal changes in arterial P CO 2 (Pezzuto et al, 2018).…”
Section: Hypoxic Breathingmentioning
confidence: 99%
“…At high altitude, in resting conditions, signs of altered diastolic but preserved or enhanced systolic RV function have been described in chronic [61] or acute hypoxic conditions [62,63]. RV seems thus to tolerate hypoxic conditions.…”
Section: Right Ventriclementioning
confidence: 99%
“…RV seems thus to tolerate hypoxic conditions. However, a recent study showed inhomogeneous RV contraction in hypoxia but not during exercise, suggesting that hypoxic stress is not trivial [63]. How much this could account for altered RV maximal outflow remains unknown as studies on right ventricular function during hypoxic exercise are sorely lacking [64].…”
Section: Right Ventriclementioning
confidence: 99%